Anticipating uncertainty and irrevocable decisions: provider perspectives on implementing whole-genome sequencing in critically ill children with heart disease. (November 2018) - Char, Danton; Lee, Sandra Soo-Jin; Magnus, David; Cho, Mildred
Abstract Purpose To investigate the potential impacts of whole-genome sequencing (WGS) in the pediatric critical-care context, we examined how clinicians caring for critically ill children with congenital heart disease (CHD) anticipate and perceive the impact of WGS on their decision-making process and treatment recommendations. Methods We conducted semistructured in-person and telephone interviews of clinicians involved in the care of critically ill children with CHD at a high-volume pediatric heart center. We qualitatively analyzed the transcribed interviews. Results In total, 34 clinicians were interviewed. Three themes emerged: (i) uncertainty about the accuracy of WGS testing and adequacy of testing validation; (ii) the use of WGS to facilitate life-limiting decisions such as futility, rationing, and selective prenatal termination; and (iii) moral distress over using WGS with a lack of decision support. Conclusion Despite uncertainty about WGS testing, the interviewed clinicians were using, and anticipated expanding the use of, WGS results to justify declarations of futility, withdrawal of care, and rationing in critically ill children with CHD. This situation is causing moral distress in providers who have to make high-stakes decisions involving WGS results, with only partial understanding of them. Decision support for clinicians, and discussion with families of the risks of using WGS for rationing or withdrawal, is needed.